Analisis Strategi Pemasaran Untuk Meningkatkan Daya Saing Perusahaan Manufaktur (Studi Kasus Pada PT Maraja Mediatama Indonesia) - Rukaiyah, St; Shaleha, Anita; Arief, Abdul Samad (Jurnal Online Manajemen ELPEI, 2025)
This study uses a descriptive quantitative research approach with the aim of explaining the marketing strategy to improve the competitiveness of manufacturing companies at PT Maraya Mediatama Indonesia by using SWOT analysis. The subjects in this study were employees and customers of PT Maraya Mediatama Indonesia. Using data collection techniques through observation, interviews and documentation. The analysis method used in this research is SWOT analysis. This analysis is based on logic that can maximize strengths (Strengths) and opportunities (Opportunities), but can simultaneously minimize weaknesses (weaknesses) and threats (Threats). The results of this study start from formulating a SWOT matrix so as to obtain an SO strategy, namely maintaining affordable prices, expanding market share, maintaining the quality and quality of service and maintaining the quality of labor / HR, WO strategy, namely increasing promotional activities, trying to increase the number of human resources, ST strategy, namely improving product quality and service quality and improving the quality of human resources and WT strategy, namely further improving the quality and quality of service to customers and developing new strategies; formulating the IFE (Internal Factor Evaluation) Matrix so that the total score of strengths (strengths) is 2.99 and the total score of weaknesses (weaknesses) is 0.40. So for the difference in strengths and weaknesses obtained, the strengths and weaknesses are obtained. So that the difference between strengths and weaknesses is 2.59; formulate the EFE (External Factor Evaluation) matrix so that the total score of opportunities is 2.62 and the total score of threats is 0.5. So that the difference between opportunities and threats is obtained 2.12; formulate the SPACE matrix so that PT Maraja Mediatama Indonesia is located in the aggressive quadrant. Where the company can use its internal strengths to take advantage of external opportunities; next is to formulate the IE matrix so that the position of PT Maraja Mediatama Indonesia is in a position to hold and maintain; and the last is to formulate the QSPM matrix. Based on the results of the TAS calculation, the most desirable and prioritized strategy to be carried out is to improve product quality and service quality and improve the quality of human resources with a TAS score of 6.634. The second strategy is to further improve the quality and quality of service by developing new strategies with a TAS score of 6.145. The third strategy is to increase promotional activities and the number of human resources with a TAS score of 6.382. Furthermore, maintaining affordable prices and expanding market share can be used to attract consumers with a TAS score of 6.076. So it can be concluded that the prioritized strategy is to improve product quality and service quality and improve the quality of human resources so as to produce products that can attract the purchasing power of customers / consumers.